Correction: Entamoeba lysyl-tRNA Synthetase Contains a Cytokine-Like Domain with Chemokine Activity towards Human Endothelial Cells. - Manuel Castro de Moura; Francesc Miro; Jung Min Han; Sunghoon Kim; Antonio Celada; Lluís Ribas de Pouplana (Public Library of Science (PLoS), 2024)
[This corrects the article DOI: 10.1371/journal.pntd.0001398.].